Governing Smart Cities: An Empirical Analysis. (December 2016) - Dameri, Renata Paola; Benevolo, Clara
Smart cities (SCs) are a recent but emerging phenomenon, aiming at using high technology and especially information and communications technology (ICT) to implement better living conditions in large metropolises, to involve citizens in city government, and to support sustainable economic development and city attractiveness. The final goal is to improve the quality of city life for all stakeholders. Until now, SCs have been developing as bottom-up projects, bringing together smart initiatives driven by public bodies, enterprises, citizens, and not-for-profit organizations. However, to build a long-term smart strategy capable of producing better returns from investments and deciding priorities regarding each city, a comprehensive SC governance framework is needed. The aim of this paper is to collect empirical evidences regarding government structures implemented in SCs and to outline a framework for the roles of local governments, nongovernmental agencies, and administrative officials. The survey shows that no consolidated standards or best practices for governing SCs are implemented in the examined cities; however, each city applies its own governance framework. Moreover, the study reveals some interesting experiences that may be useful for involving citizens and civil society in SC governance.